Regulation of MST complexes and activity via SARAH domain modifications. (30th April 2021) - Karchugina, Sofiia; Benton, Dorothy; Chernoff, Jonathan
Abstract : Three elements of the Hippo tumor suppressor pathway — MST1/2, SAV1, and RASSF1–6 — share in common a C-terminal interaction motif termed the SARAH domain. Proteins containing this domain are capable of self-association as homodimers and also of trans-association with other SARAH domain containing proteins as well as selected additional proteins that lack this domain. Recently, the association of MST1/2 with itself or with other proteins has been shown to be regulated by phosphorylation at sites near or within the SARAH domain. In this review, we focus on recent findings regarding the regulation of such MST1/2 interactions, with an emphasis on the effects of these events on Hippo pathway activity.